2011
DOI: 10.1214/10-ssy009
|View full text |Cite
|
Sign up to set email alerts
|

An ODE for an overloaded X model involving a stochastic averaging principle

Abstract: We study an ordinary differential equation (ODE) arising as the many-server heavy-traffic fluid limit of a sequence of overloaded Markovian queueing models with two customer classes and two service pools. The system, known as the X model in the call-center literature, operates under the fixed-queue-ratio-with-thresholds (FQR-T) control, which we proposed in a recent paper as a way for one service system to help another in face of an unanticipated overload. Each pool serves only its own class until a threshold … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
51
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(51 citation statements)
references
References 16 publications
0
51
0
Order By: Relevance
“…The downward rates are 1 + ≡ 1 1 m 1 + 1 2 z 1 2 + 2 2 m 2 − z 1 2 + 1 q 1 and r + ≡ 2 (16) As in §7.1 of Perry and Whitt [37], we identify important subsets of the state space ≡ 0 Let D be a random variable that has the steady-state limiting distribution of the FTSP D s as s → and let 1 2 ≡ P D > 0 (18) That is, 1 2 is the probability that the stationary FTSP associated with ∈ is strictly positive. It turns out that D and 1 2 are well defined throughout .…”
Section: A Series Of Papersmentioning
confidence: 97%
See 4 more Smart Citations
“…The downward rates are 1 + ≡ 1 1 m 1 + 1 2 z 1 2 + 2 2 m 2 − z 1 2 + 1 q 1 and r + ≡ 2 (16) As in §7.1 of Perry and Whitt [37], we identify important subsets of the state space ≡ 0 Let D be a random variable that has the steady-state limiting distribution of the FTSP D s as s → and let 1 2 ≡ P D > 0 (18) That is, 1 2 is the probability that the stationary FTSP associated with ∈ is strictly positive. It turns out that D and 1 2 are well defined throughout .…”
Section: A Series Of Papersmentioning
confidence: 97%
“…The AP takes place only in the set . In Theorem 6.1 of Perry and Whitt [37] we showed that positive recurrence of the FTSP, and thus the set , depends only on the constant drift rates in the two regions:…”
Section: A Series Of Papersmentioning
confidence: 98%
See 3 more Smart Citations